The Impact of Mixed Land Use on Residential Property Values - Hans R.A. Koster; Jan Rouwendal (Tinbergen Institute, 2010)
Contemporary European urban planning policies aim to mix land uses in compact neighbourhoods. It is presumed that mixing land uses yields socio-economic benefits and therefore has a positive effect on housing values. In this paper, we investigate the impact of mixed land use on housing values using semiparametric estimation techniques. We demonstrate that a diverse neighbourhood is positively valued by households. There are various land use types which positively affect house prices, e.g. business services and leisure. Land uses that are incompatible with residential land use are, among others, manufacturing and wholesale. It appears that households are willing to pay up to 6 percent more for a house in a mixed neighbourhood than for an otherwise comparable house in a monofunctional area. We also show that there is substantial heterogeneity in willingness to pay for mixed land use. For example, apartment occupiers are willing to pay almost 25 percent more for diversity than households living in detached housing.
Keywords: R14; R30; R52; R58; 330; Mixed land use; diversity; hedonic price analysis; semiparametric estimation; Bauleitplan; Wohnimmobilien; Immobilienpreis; Willingness to pay; Hedonischer Preisindex; Nichtparametrisches Verfahren; Schätzung; Rotterdam